Subject Lessons : Hegel, Lacan, and the Future of Materialism - Zupančič, Alenka; McGowan, Todd; Radnik, Borna; Cole, Andrew; Dolar, Mladen; Rothenberg, Molly Anne, 1952-; Gorelick, Nathan; Van Wert, Kathryn; Johnston, Adrian; Žižek, Slavoj; Sbriglia, Russell, 1982- (Book collections on Project MUSE., 2020)
"This collection of eleven philosophical essays addresses current trends in materialist philosophy dealing with subject-object relations, amounting to a polemical corrective that insists on the organizing role of the subject within materialist thought"--